2020
DOI: 10.4274/jtgga.galenos.2019.2019.0051
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal microbiota and human papillomavirus: a systematic review

Abstract: Accumulating evidence indicates the potential correlation between the vaginal microbioma and the acquisition and persistence of human papillomavirus (HPV) infection. This study aims to demonstrate the potential relationship through a systematic review of the current literature. A search was conducted on the following medical databases: PubMed and Scopus. Nineteen studies met the inclusion criteria and were incorporated in the present review. A total of 12.204 patients and their demographic characteristics were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…However, its pathophysiological role in the context of HPV infection was unknown until recently. Recent studies have suggested that the cervicovaginal microbiome (CVM) plays an important role in the persistence of HR-HPVs and the occurrence risks of CIN2/3 and invasive cancers by influencing the natural history of HPV infection, and could serve as a complementary therapeutic target to prevent the occurrence of high-grade intraepithelial lesions leading to invasive cancers (126)(127)(128)(129)(130).…”
Section: Cervicovaginal Microbiome and Precancerous Lesion Occurrence Risksmentioning
confidence: 99%
“…However, its pathophysiological role in the context of HPV infection was unknown until recently. Recent studies have suggested that the cervicovaginal microbiome (CVM) plays an important role in the persistence of HR-HPVs and the occurrence risks of CIN2/3 and invasive cancers by influencing the natural history of HPV infection, and could serve as a complementary therapeutic target to prevent the occurrence of high-grade intraepithelial lesions leading to invasive cancers (126)(127)(128)(129)(130).…”
Section: Cervicovaginal Microbiome and Precancerous Lesion Occurrence Risksmentioning
confidence: 99%
“…Some of these changes are responsible for increasing the levels of mucin-degrading enzymes, which may play a role in the degradation of the mucous layer that covers the vaginal and cervical epithelium and endocervical mucus ( 20 , 21 ). There is evidence of HPV evasion or infection mechanisms that support that microorganisms such as Sneathia , Anaerococcus , Fusobacterium , and Gardnerella are implicated with higher frequency and severity of disease, potentially resulting in precancerous and cancerous cervical lesions ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these changes are responsible for increasing the levels of mucin-degrading enzymes, which may play a role in the degradation of the mucous layer that covers the vaginal and cervical epithelium and endocervical mucus (20,21). There is evidence of HPV evasion or infection mechanisms that support that microorganisms such as Sneathia, Anaerococcus, Fusobacterium and Gardnerella are implicated with higher frequency and severity of disease, potentially resulting in pre-cancerous and cancerous cervical lesions (22) However, these findings are not uniform across studied populations, because, despite the fact that Latin American countries have a high prevalence of HPV and cervical cancer are one of the main causes of death in women in these areas (3,(23)(24)(25), including Mexico (7,9), most of the studies have been conducted in developed countries (26). Likewise, the projected demographic changes in Latin America imply that the current burden of new cervical cancer cases will increase in the next 20 years (2,27).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these changes are responsible for increasing the levels of mucin-degrading enzymes, which may play a role in the degradation of the mucous layer that covers the vaginal and cervical epithelium and endocervical mucus (20, 21). There is evidence of HPV evasion or infection mechanisms that support that microorganisms such as Sneathia, Anaerococcus, Fusobacterium and Gardnerella are implicated with higher frequency and severity of disease, potentially resulting in pre-cancerous and cancerous cervical lesions (22)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation